Role of Atorvastatin on Endothelial Cells and Endothelial Progenitor Cells in Cardiovascular Disease - Sampath Kumar, Sujeetha Purushothaman, Papitha Ponnaiya, Keerthi Kishor, Vijaya Anand (Journal of Applied Pharmaceutical Science, 2016)
The endothelium plays a key role in haemostatic balance. Endothelial progenitor cells (EPCs) are involved in the maintenance of endothelial haemostasis and in the process of blood vessel formation. Cardiovascular disease (CVD) is associated with reduced numbers and dysfunction of endothelial cells (ECs) and EPCs. Inhibition of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-Co-A) reductase helps in restoring of EPCs and improvement of vascular function. This review underlines the pleiotropic effects of atorvastatin on ECs and EPCs.
Keywords: Endothelial cells, Endothelial Progenitor cells, Atherosclerosis, Atorvastatin.